Perspectives of Phage Therapy in Non-bacterial Infections - Górski, Andrzej; Bollyky, Paul L.; Przybylski, Maciej; Borysowski, Jan; Międzybrodzki, Ryszard; Jończyk-Matysiak, Ewa; Weber-Dąbrowska, Beata (Frontiers in Microbiology, 2019)
While the true value of phage therapy (PT) in human bacterial infections still awaits formal confirmation by clinical trials, new data have been accumulating indicating that in the future PT may be applied in the treatment of non-bacterial infections. Thus, “phage guests” may interact with eukaryotic cells and such interactions with cells of the immune system may protect human health (Guglielmi, 2017) and cause clinically useful immunomodulatory and anti-inflammatory effects when administered for therapeutic purposes (Górski et al., 2017; van Belleghem et al., 2017). Recently, a vision of how these effects could translate into advances in novel means of therapy in a variety of human pathologies secondary to immune disturbances and allergy was presented (Górski et al., 2018 a). In this article we present what is currently known about anti-microbial effects of phage which are not directly related to their antibacterial action and how these findings could be applied in the future in treatment of viral and fungal infections.